L1 and its effect on EFL writing: a descriptive framework - Rizwana Wahid, Oveesa Farooq, (Opción, 2019)
This study attempts to investigate the interference of L1 on the writing of undergraduate EFL students of Saudi Arabia and aims to critically analyze their writing samples via comparative qualitative research methods. As a result, there is no helping verb in Arabic that is why they mostly do not use it in English and even if they do, they use it improperly. In conclusion, Saudi students prefer to understand their subjects, to be taught in Arabic. It is all their low motivation towards English and hindrance of L1 in its learning.